Implementing Interactive Word Wall-Assisted General Vocabulary Learning for EFL Secondary Students: A Classroom Action Research - Agustin, Helmania Herawati; Yanto, Elih Sutisna (Peneliti.net, 2024)
The acquisition of vocabulary plays a crucial role within the realm of language proficiency, as words are assimilated in a manner that facilitates comprehension, oral expression, and subsequently, reading and written communication in the English language. One of the pedagogical approaches that can be employed for vocabulary instruction is the utilization of interactive word walls. The objective of this study is to investigate the impact of interactive word walls on students' comprehension and learning experience in vocabulary acquisition through the utilization of word wall approaches. The primary objective of this study is to ascertain the viewpoints of students on the utilization of this technique for the purpose of acquiring new vocabulary. The research design employed a classroom action approach. The findings of this study indicate that the utilization of word walls in vocabulary acquisition can significantly impact learners' comprehension of vocabulary learning, particularly in the aspect of word class identification and comprehension of novel vocabulary terms. Interactive word walls have been found to elicit a favorable response from pupils due to the facilitation of vocabulary acquisition. Nonetheless, there exist drawbacks associated with the utilization of interactive word walls. One of the primary challenges encountered by students while utilizing interactive word walls is to the acquisition of new vocabulary and the pronunciation of unfamiliar terms. This difficulty arises from their limited proficiency in effectively utilizing dictionaries and their lack of familiarity with the process of searching for new vocabulary entries within such resources. The efficacy of the interactive word wall method in enhancing students' vocabulary acquisition can be inferred from the evidence. This pedagogical approach facilitates the identification and comprehension of word classes, hence fostering a more effective vocabulary learning experience. Furthermore, the interactive nature of the strategy successfully engenders student engagement and enthusiasm towards vocabulary acquisition